Diseño de un modelo de negocio para la sostenibilidad de la comercialización de vehículos eléctricos e híbridos en Colombia (2019)
This document contents the description of automotive commercial activity and the commercialization of electric and hybrid vehicles in Colombia (2019). During the development of the monograph, a market study survey was carried out, in order to determine the expectations of potential customers of electric and hybrid vehicles in Colombia. With the use of this information and the direct visit to dealerships of brands such as: Volvo, KIA, BYD, Renault, BMW, Mercedes Benz, Nissan and Audi, key activities and resources were proposed to make marketing sustainable.